## The problem

i am not understanding where the solution gets to the x= answer could you please explain to me why it is that way to me it is very confusing.

## Answer provided by our tutors

The whole point of the solving is to get the variable terms (terms with 'x') on the left hand side of the equation and all the numbers on the right hand side of the equation.

First we perform all the operations to transform

-3(x+5)=5x-7(2x+5)

to

-3x - 15 = 5x - 14x - 35

-3x - 15 = -9x - 35

Then we move '-9x' to the right side and '-15' to the left side:

-3x + 9x = -35 + 15

6x = -20

Then we divide both sided by '6':

x = -20/6

x = - 10/3

x = -3 1/3

You can obtain an explanation for any step by clicking on it. Please note that you cannot click on the very first expression, which is the original problem. Quite often, several transformations will be performed within the same step. Use the explanation navigation buttons to step through all of them: